2021
DOI: 10.1038/s41467-021-27172-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell-fate transition and determination analysis of mouse male germ cells throughout development

Abstract: Mammalian male germ cell development is a stepwise cell-fate transition process; however, the full-term developmental profile of male germ cells remains undefined. Here, by interrogating the high-precision transcriptome atlas of 11,598 cells covering 28 critical time-points, we demonstrate that cell-fate transition from mitotic to post-mitotic primordial germ cells is accompanied by transcriptome-scale reconfiguration and a transitional cell state. Notch signaling pathway is essential for initiating mitotic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 111 publications
3
55
1
1
Order By: Relevance
“…7 A, Supplemental Table S9 ). Gene expression analysis revealed that ATRA significantly differentially regulated the expression of 231 germ cell development genes that were identified in a recent single-cell RNA-seq publication ( Zhao et al, 2021 ). Specifically, ATRA upregulated genes first expressed during germ cell development stages, including peaks of DEGs associated with the quiescent prospermatogonia, differentiating and differentiated spermatogonia, and pachytene spermatocyte stages.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 A, Supplemental Table S9 ). Gene expression analysis revealed that ATRA significantly differentially regulated the expression of 231 germ cell development genes that were identified in a recent single-cell RNA-seq publication ( Zhao et al, 2021 ). Specifically, ATRA upregulated genes first expressed during germ cell development stages, including peaks of DEGs associated with the quiescent prospermatogonia, differentiating and differentiated spermatogonia, and pachytene spermatocyte stages.…”
Section: Resultsmentioning
confidence: 99%
“…7 ATRA and MEHP altered the transcriptional profile of genes first expressed during germ cell development stages. A. Germ cell-specific gene expression clusters were extracted from Zhao et al (2021) , and are displayed on the x-axis in order of developmental stage. DEG lists for each of the three RNA-seq analyses reported in this paper (MEHP vs vehicle, ATRA vs vehicle, and MEHP + ATRA vs vehicle) were searched for genes first expressed in any germ cell RNA-seq cluster, and the number of genes up- or downregulated per cluster is displayed on the chart.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the high heterogeneity and low cell number of ProSG and SSCs, it is challenging to study their characteristics (Du et al, 2021;Tan et al, 2020b). Although several studies have been devoted to distinguishing their subtypes and identifying some subtypes of ProSG and SSCs, much is still unknown about their subtypes (Guo et al, 2018;Guo et al, 2017;Guo et al, 2021;Tan et al, 2020b;Tan and Wilkinson, 2020;Zhao et al, 2021). In this study, we identi ed three cell types using the scRNA-seq technique: ProSG, SSCs, and differentiating spermatogonia.…”
Section: Discussionmentioning
confidence: 99%